Candida azymoides sp. n., uma espécie de levedura de frutas tropicais e larvas de Anastrepha mucronota (Diptera: Tephritidae) (Lundiana: International Journal of Biodiversity, 2007)
Four strains of the new species Candida azymoides were isolated from larvae of Anastrepha mucronota (Diptera: Tephritidae) collected from ripe fruits of Peritassa campestris (“bacupari”, Hippocrateaceae) in the state of Tocantins and from ripe fruits of Eugenia uniflora (“pitanga”, Myrtaceae) collected in the state of Sergipe, Brazil. Candida azymoides is the sister species to C. azyma in the Wickerhamiella clade, in the Saccharomycetes. The type strain is Candida azymoides UFMG-R287 (CBS 10508).Keywords: Candida azymoides, new yeast species, tropical fruits, Anastrepha mucronota.